2021
DOI: 10.1007/s40139-021-00228-y
|View full text |Cite
|
Sign up to set email alerts
|

The Pathobiological Basis for Thrombotic Complications in COVID-19: a Review of the Literature

Abstract: Purpose of Review COVID-19 has rapidly evolved into a global pandemic infecting over two hundred and forty-four million individuals to date. In addition to the respiratory sequelae and systemic infection that ensues, an alarming number of micro and macrovascular thrombotic complications have been observed. This review examines the current understanding of COVID-19-associated thrombotic complications, potential mechanisms, and pathobiological basis for thromboses development. Recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 97 publications
(147 reference statements)
1
3
0
Order By: Relevance
“…Therefore, it could be speculated that the suppression of HO- The PLAT gene was found in the networks of hyperglycemia, CVD, diabetic neuropathy, and retinopathy. This is consistent with data on the important role of fibrinolysis disorders in the development of diabetic vascular complications [211] and COVID-19 [212].…”
Section: Ctsl-related Networksupporting
confidence: 92%
“…Therefore, it could be speculated that the suppression of HO- The PLAT gene was found in the networks of hyperglycemia, CVD, diabetic neuropathy, and retinopathy. This is consistent with data on the important role of fibrinolysis disorders in the development of diabetic vascular complications [211] and COVID-19 [212].…”
Section: Ctsl-related Networksupporting
confidence: 92%
“…SARS-CoV-2 infection has also been reported to cause pulmonary vascular endothelial inflammation and subsequent thrombosis [13][14][15][16][17][18]. It has been described as causing an inflammatory, prothrombotic, hypofibrinolytic state [19,20]. However, this is possibly the case in all viral infections [21].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the prognostic value of initial routine laboratory values, the prognostic value of D-dimers has been described extensively [ 23 , 24 ]. Initial hypercoagulability with the transition to the consumptive stage of disseminated intravascular coagulopathy (DIC) has been reported [ 25 , 26 , 27 ]. Moreover, Gatto et al showed a frequent occurrence of pulmonary embolism between days 1 and 47 of hospitalization, occurring in the majority on day 10 [ 27 ].…”
Section: Discussionmentioning
confidence: 99%